Breaking A Communication Barrier: The Effect of Visual Aids in Food Preparation on Job Attitudes and Performance. (May 2013) - Madera, Juan M.; Dawson, Mary; Neal, Jack A.; Busch, Kristin
Given the diverse workforce of the hospitality industry, language difficulties continue to create communication barriers for both employers and immigrant workers. As a result, these barriers have negative effects on job performance and organizational attitudes. In an effort to provide solutions, this article examines the effect of using pictures on job performance, task satisfaction, and job commitment when communication barriers exist in a food industry operation context. The results of this experimental study demonstrated that the performance of workers who used pictures when producing a dish was evaluated higher on dimensions of time, quality, and accuracy than that of workers who did not use pictures. Additionally, the participants who were given pictures reported higher task satisfaction and commitment than those who were only provided an abstract recipe.